2022
DOI: 10.1177/11779322221088796
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis for Identification of Therapeutic Targets and Prognostic Signatures in Non-Small Cell Lung Cancer

Abstract: Differential expressions of certain genes during tumorigenesis may serve to identify novel manageable targets in the clinic. In this work with an integrated bioinformatics approach, we analyzed public microarray datasets from Gene Expression Omnibus (GEO) to explore the key differentially expressed genes (DEGs) in non-small cell lung cancer (NSCLC). We identified a total of 984 common DEGs in 252 healthy and 254 NSCLC gene expression samples. The top 10 DEGs as a result of pathway enrichment and protein–protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Prominent examples in this regard include histone deacetylase inhibitors (HDACs) and DNA methyltransferase inhibitors (DNMTs). It has been observed that HDAC inhibitors, such as vorinostat (SAHA) [ 140 ], panobinostat (LBH589) [ 141 ], belinostat (PXD-101) [ 142 ], and trichostatin A (TSA) [ 143 ], can reduce the expression of genes associated with tumor growth and metastasis. Additionally, DNMT inhibitors, such as decitabine and azacitidine, have revealed their potential by reversing gene promoter hypermethylation, a hallmark of cancer [ 144 ].…”
Section: Detailed Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples in this regard include histone deacetylase inhibitors (HDACs) and DNA methyltransferase inhibitors (DNMTs). It has been observed that HDAC inhibitors, such as vorinostat (SAHA) [ 140 ], panobinostat (LBH589) [ 141 ], belinostat (PXD-101) [ 142 ], and trichostatin A (TSA) [ 143 ], can reduce the expression of genes associated with tumor growth and metastasis. Additionally, DNMT inhibitors, such as decitabine and azacitidine, have revealed their potential by reversing gene promoter hypermethylation, a hallmark of cancer [ 144 ].…”
Section: Detailed Results and Discussionmentioning
confidence: 99%
“…Trichostatin A (TSA) has been identified as a promising therapeutic option for NSCLC by multiple studies. Erkin et al determined that trichostatin A, pracinostat, TGX-221, PHA-793887, AG-879, and IMD0354 had the potential to reverse the expression of the differentially expressed genes (DEG) genes such as CDC20 , AURKA , CDK1 , EZH2 , and CDKN2A in NSCLC [ 143 ]. Sindo et al suggested that quisinostat (JNJ-2648158) and TSA can induce G1 arrest and inhibit migration of A549 cells, as well as improve mitochondrial respiration and elevate CLDN-7 expression.…”
Section: Detailed Results and Discussionmentioning
confidence: 99%
“…Docetaxel, palbociclib, and angiogenesis-inhibitor were among the extensively used compounds for the treatment of tumor, as determined by their scores. Other drugs/molecules, such as MK-1775 [ 34 , 35 ], MK-5108 [ 36 ], fenbendazole [ 37 , 38 ], albendazole [ 39 ], BAY-K8644 [ 40 ], evodiamine [ 41 ], purvalanol-a [ 42 ], mycophenolic-acid [ 43 ], PHA-793887 [ 44 ], cyclopamine [ 45 ], is a possible treatment for lung adenocarcinoma (Tables 5 , 6 ). To determine the therapeutic potential of these drugs/molecules in patients with lung adenocarcinoma with high EZH2 expression, additional research is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Docetaxel, palbociclib, and angiogenesis-inhibitor were among the extensively used compounds for the treatment of tumor, as determined by their scores. We have identified some potential drugs or molecules for the treatment of lung adenocarcinoma by reading the literature, such as MK-1775 [ 34 , 35 ], MK-5108 [ 36 ], fenbendazole [ 37 , 38 ], albendazole [ 39 ], BAY-K8644 [ 40 ], evodiamine [ 41 ], purvalanol-a [ 42 ], mycophenolic-acid [ 43 ], PHA-793887 [ 44 ], and cyclopamine [ 45 ] (Tables 5 , 6 ). Of interest is the WEE1 inhibitor MK-1775, which has shown potential chemotherapy or radiotherapy sensitivity in preclinical models, particularly, although not exclusively, in p53 mutated or deficient cancer cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%